Late Paleozoic glacial episodes in Gondwanaland reflected in transgressive- regressive depositional sequences in Euramerica - Veevers, J. J.; Powell, C. McA (1987)
The Late Paleozoic glaciation of Gondwanaland comprised two short episodes, in the Famennian (I) and Visean (II) confined to Brazil and adjacent northwest Africa, and a long episode that started in the Namurian (IIIA) of eastern Australia and Bolivia/Argentina, expanded to cover much of Gondwanaland in the Stephanian/Asselian (IIIB), and collapsed in the early Sakmarian (IIIC). Dropstones in eastern Australia indicate that small ice centers lingered to the Kazanian. Across the belt of low latitudes north of Gondwanaland, short-ranging fossils in widespread shallow-marine and paralic deposits indicate synchronous deposition of transgressive-regressive sequences in different parts of Euramerica. These sequences correlate with glacial events in Gondwanaland at three levels: (a) four major regressions in Euramerica, in the Famennian (1), Visean (2), Namurian (3), Stephanian (4), and the Tastubian transgression that preceded the Sterlitamakian regression (5), also recorded in Gondwanaland, correlate with glacial episodes I, II, and IIIA, IIIB, and IIIC; (b) the time-interval of cyclothemic deposition in Euramerica (Brigantian or latest Visean to Sterlitamakian) correlates with that of glacial episode III; and (c) the dominant period of the Euramerican cyclothems, as estimated from the Middle and Late Pennsylvanian deposits of the mid-continent of North America, and of the thickest known Gondwanaland glacigenic sediment (the earliest Permian Lyons Group of Western Australia) is 0.4 Ma, equivalent in turn to the long orbital-eccentricity period of the Quaternary ice age, and the dominant period of fluctuation of the late Miocene Antarctic ice cap. The three levels of correlations confirm Wanless and Shepard's (1936) hypothesis that the Late Paleozoic cyclothems are controlled largely by sea-level fluctuations related to the Gondwanaland glaciation.